2006
DOI: 10.1353/pla.2006.0012
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Academic Library: Undergraduate Research Behavior in a Library Without Books

Abstract: This study examines undergraduate students' research habits in a strictly electronic library environment at a large public university. Unlike most information commons, the campus' electronic library is not housed within a traditional library space and provides access to electronic research materials exclusively. This study finds that undergraduate students in this electronic library rely primarily on Internet sites and online instruction modules (for example Blackboard or WebCT) for their research needs rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…22,30,31 However, usage of Wikipedia for course projects in this study was considerably less than in a recent multi-institution study of undergraduate students. In that study, 52% of respondents used Wikipedia always or frequently during the course-related research process.…”
Section: Methodsmentioning
confidence: 63%
“…22,30,31 However, usage of Wikipedia for course projects in this study was considerably less than in a recent multi-institution study of undergraduate students. In that study, 52% of respondents used Wikipedia always or frequently during the course-related research process.…”
Section: Methodsmentioning
confidence: 63%
“…Several studies indicate that university websites, including websites of university libraries, are among the most widely used sources of information, and materials contained on these websites are important support for students in their learning (Biddix et al, 2011;Holman, 2011;Jones, Johnson-Yale, Millermaier, & Pérez, 2008;Kim, 2011;Malliari, Korobili, & Zapounidou, 2011;Simões & Soares, 2010;Van Scoyoc & Cason, 2006). According to Wu and Chen (2012), graduate students of one Taiwanese university preferred to use the university library website as their primary search source rather than the Internet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research from the Pew Internet & American Life Project reported that ''nearly threequarters (73 percent) of college students reported using the Internet for research more than the campus library'' (Jones, 2002). Other findings suggest a vast majority of students turning to the internet first for academic research (Griffiths and Brophy, 2005;Van Scoyoc, 2006). Nwagwu et al (2009) asserted that the infusion of the internet into higher education has intensified access to archived information sources from various parts of the world, thus forming the first point of call for students and others when they seek information.…”
Section: Introductionmentioning
confidence: 99%